Institutional Theory of M. Olson: «The Principle of Expansion» - Sukharev Oleg S. (Журнал институциональных исследований, 2017)
The article explores the basic concepts of Mancur Olson's special interest groups theory, which demonstrates the «logic of collective action», elaborated using John Commons’ «extension principle». Such a perspective allows us to make some clarifications on the wording of this theory, provided that the criterion (rule) according to which agents behave in the group, when comparing individual and collective (group) benefits, is changing. If superiority of the individual benefit over the collective benefit is chosen as the target function, then for the maximum value of this criterion the relative change in the ratio between the individual benefits and total costs will be equal to the difference of relative change in the average values of the units of the public good produced and unit costs. Striving for the greatest individual benefit may impair the well-being of the economic system that is seen in the «prisoner's dilemma». However, the growth of the group does not always lead to reduced efficiency, which depends on input criteria. In other words, the assessment of the situation in the economy is determined by the «institutional function» of economic science, which gives a criterion for the implementation of the verdict. The «extension principle» is useful in the interpretation of economic policy, especially in the aspect of modification of the principle of «objectives and instruments». However, there is a limitation on the use of the principle associated with the «cobra effect» and the «expectations trap». In addition, there is a conflict of the «principle оf the theory presumption» according to which the power of the economic theory is determined by the solution of a larger number of tasks with less tools, and the «extension principle», requiring expansion of facilities and concentration of power. With regard to economic policy, this means the selection of tools from a wide set of measures of impacts with the rationale for their effectiveness (efficiency), is addressed not only to the parameters of influence, but also to the broader characteristics of the economic system.